Resolution of mtDNA mixtures using a probe capture next generation sequencing system and custom analysis software. Issue 1 (December 2019) - Shih, Shelly; Lim, Jessica; Wisner, Mary; Erlich, Henry; Calloway, Cassandra
Abstract: To analyze crime scene evidence with degraded DNA, we have designed a probe capture Next Generation Sequencing system for targeted enrichment for both nuclear SNP markers and for the entire mitochondrial DNA genome. This probe capture NGS system was used to capture and sequence both nuclear SNPs and mtDNA markers from the same DNA shotgun library. Version 1 of the SNP panel (SNPv1.0; 451 SNPs) includes identity informative, ancestry informative, phenotypic informative, haploid chromosomal, tri-and tetra-allelic and microhaplotype SNPs. Version 2 of the SNP panel (SNPv2.0; 436 SNPs) includes the same categories of SNPs as those present in version 1 of the panel with the exclusion of phenotypic informative SNPs. These two probe panels, along with our whole mitochondrial genome probe panel, were used to analyze mixtures using DNA from control cell lines, simulated biological evidence samples, and study subjects. The sequence data was analyzed with NextGENe®, GeneMarker®HTS software and, for the mtDNA sequences, with the phylogenetics based software Mixemt. The probe capture NGS system can capture and sequence fragments as short as 35 bp. For the SNP panel, the minor contributor could be detected down to a 2.5% minor contribution with a 1 ng DNA input. Using the Mixemt software for the analysis of mtDNA mixtures, we were able to detect the minor contributor as low as 0.31%. Moreover, Mixemt could de-convolute three person mixtures as well as two person mixtures with similar proportions.